Analisis Wacana Kritis Sara Mills dalam Cerpen Sepasang Mata Dinaya yang Terpenjara - Wiwit Sariasih; Yumna Rasyid; Miftahulkhairah Anwar (Universitas Mulawarman, 2023)
This research aims to describe the subject-object and writer-reader positions in the short story